ID3 mediates BMP2-induced downregulation of ICAM1 expression in human endometiral stromal cells and decidual cells - Luo, Jin; Wang, Yaqin; Chang, Hsun-Ming; Zhu, Hua; Yang, Jing; Leung, Peter C. K. (Frontiers in Cell and Developmental Biology, 2023)
Recurrent pregnancy loss (RPL) remains an unsolved problem in obstetrics and gynecology, and up to 50% of RPL cases are unexplained. Unexplained RPL (uRPL) is widely considered to be related to an aberrant endometrial microenvironment. BMP2 is an important factor involved in endometrial decidualization and embryo implantation, and intercellular adhesion molecule 1 (ICAM1) is a critical inflammatory regulator in the endometrium. In our study, we demonstrate that endometrial samples obtained from uRPL patients have significantly lower BMP2 and higher ICAM1 levels than fertile controls. To investigate the effects of BMP2 on ICAM1 expression as well as the underlying molecular mechanisms in the human endometrium, we used immortalized human endometrial stromal cells (HESCs) and primary human decidual stromal cells (HDSCs) as study models. Our results showed that BMP2 significantly decreased ICAM1 expression by upregulating DNA-binding protein inhibitor 3 (ID3) in both HESCs and HDSCs. Using kinase receptor inhibitors (dorsomorphin homolog 1 (DMH-1) and dorsomorphin) and siRNA-mediated inhibition approaches, we demonstrated that BMP2-induced upregulation of ID3 and downregulation of ICAM1 expression is mediated by the ALK3-SMAD4 signaling pathway. These findings deepen our understanding of a novel mechanism by which BMP2 regulates ICAM1 in the human endometrium, which provides insights into potential therapeutics for unexplained RPL.